The 12 most influential photographs of all time - Ventura, Marne (Most influential., 2018)
Highlights the twelve most influential photographs in history, from Eadweard Muybridge developing stop-motion photography to Louie Favorite photographing a reunion between a military mother and her daughter. Features fact boxes, statistics, a glossary, and resources for further information.